Modal Sosial Yang Di Miliki Anggota Kelompok Kerja (POKJA) Perilaku Hidup Bersih dan Sehat (PHBS) Dalam Upaya Penerapan Perilaku Hidup Bersih dan Sehat : (Studi Deskriptif Di Sekolah Menengah Pertama Negeri 107 Jakarta) - Sherliany, Annisa; Bantarti, Wisni (UI Scholars Hub, 2015)
The purpose of this research to describe the social capital that is owned by the working group members of PHBS of SMP Negeri 107 Jakarta in an effort to implement a clean and healthy living behavior. This research uses a qualitative approach and is a descriptive research through data collection techniques in-depth interviews, observation, and literature study. The results of this research shows that social capital is owned by members of the working group of PHBS of SMP Negeri 107 Jakarta can support its success in an effort to implement clean and healthy living behavior.